Saussure’s Value(s) - Joseph, John (Recherches sémiotiques / Semiotic Inquiry)

(untitled) (Association canadienne de sémiotique / Canadian Semiotic Association, 2014)
Valeur, value, is central to how languages are conceived in the Cours de linguistique générale, and it has been an integral part of Saussure’s intellectual legacy. This paper investigates the background to his conception of value, focussing particularly on the work of Henri Dameth, as there is evidence suggesting that Saussure attended Dameth’s lectures on political economics while a student at the University of Geneva. Several parallels are noted between the treatment of value in Dameth’s work and in the Cours. The paper also examines the role of value in Saussure’s writings prior to his lectures on general linguistics, as well as the links between the Cours and the work of Saussure’s brother, René, on an international currency, in conjunction with his role in the Esperanto movement.